Conflicts of interest in scientific publishing. (20th November 2017) - Amigo, Ignacio; Pascual‐García, Alberto
Abstract : Gold OA as a publishing model has created conflicts of interest for authors and journals that create a risk for research integrity. Alternative models of publishing and peer review could resolve some of these conflicts.